Non-gender-biased intervention approach and Kindergarten children's choice of toys at the Siliman University early childhood school - Bacarro, Perpetua Tinambacan (2001)
This study primarily investigated changes in the children's choice of toys from gender-biased to non-gender-biased choice employing an intervention approach, and as a subsidiary, whether or not there is an existence of gender bias practices among teachers in the kindergarten classes of Silliman University Early Childhood School. The intervention approach included non-gender-biased stories and song, presentation of sets biased toys as appropriate toys for every one regardless of sex, resource persons portraying non-gender-biased roles, and matching game of pictures with non-gender-biased activities. The data that supported the main study were gathered from the observation of the control and experimental kindergarten teachers' gender and non-gender-biased practices during children's play period. The findings that t6he teachers manifested passive bias practices during children's play period helped the researcher finalize the intervention approach. To determine changes of children's choice of toys, data were collected through pre and post-observation and interviews on gender and non-gender-biased choice of toys. Ten kindergarten children of the control group and ten of the experimental group at Silliman Early Childhood School were the subjects of the study. The result revealed t6hat there is an existence of strong gender-biased choice of toys among kindergarten children of the two groups during the pre-observation and interviews. However, based choice in the experimental group showed definite changes to non-gender-biased choice of toys after the administration of the non-gender-biased intervention package, while in the control group biased choice even increased a little higher. From this finding, a conclusion was drawn that appropriate intervention approaches are effective to counter gender biases among children at the kindergarten level. Recommendations are presented which are as follows: curricular and program revision at the Early Childhood and College for Early Childhood Majors at Silliman University and other institutions, seminars on gender bias awareness and sensitivity, and with some significant guidelines a replication of this study.